2018
DOI: 10.3389/fmars.2018.00412
|View full text |Cite
|
Sign up to set email alerts
|

Intertidal Biogeographic Subprovinces: Local and Regional Factors Shaping Fish Assemblages

Abstract: Intertidal zones shelter a wealth of species and natural resources, provide important ecological services, and sustain several economic activities in coastal communities. However, the tidepool fish species that inhabit the intertidal zone are subject to a wide array of impacts due to the human presence and their accessibility, creating a challenge for the mitigation of habitat loss, in particular in tropical regions where the ecology and distribution of species are poorly known. In this study, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 107 publications
2
10
0
2
Order By: Relevance
“…and Tomicodon spp. in islands compared to mainland (Andrades et al, 2018a), agreeing to the MacArthur et al (1972) "density compensation" hypothesis. Yet, as intraspecific competition increases in response to density compensation (Crowell, 1962;Pafilis et al, 2009), a FIGURE 2 | The four-leaf tree predicting the traits related to interspecific competition success of fish taxa.…”
Section: Discussionsupporting
confidence: 76%
“…and Tomicodon spp. in islands compared to mainland (Andrades et al, 2018a), agreeing to the MacArthur et al (1972) "density compensation" hypothesis. Yet, as intraspecific competition increases in response to density compensation (Crowell, 1962;Pafilis et al, 2009), a FIGURE 2 | The four-leaf tree predicting the traits related to interspecific competition success of fish taxa.…”
Section: Discussionsupporting
confidence: 76%
“…However, it does not describe well the distribution of rocky intertidal assemblages, for example, along the Pacific coast of North America (Blanchette et al, 2008) and the coast of Peru (Ibanez-Erquiaga et al, 2018), or the distribution of fish assemblages along Caribbean (Robertson & Cramer, 2014) and Mediterranean (Hattab et al, 2015) coasts. Some studies also identified smaller units nested within ecoregions (Andrades et al, 2018;Sink et al, 2005), suggesting that ecoregions are not the smallest units in marine bioregionalisation. However, as the MEOW system covers both shallow-water and deep-sea habitats, it remains unclear whether it represents the distribution of a broad range of taxonomic groups, with different depth preferences, across marine habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their importance as nursery habitats to juvenile fish fauna, including endangered species (Lobato et al., 2016), or permanent habitats for multiples species from different trophic groups (Andrades et al., 2018), and provided the constant human pressure through unregulated tourism, pollution, and coastal construction among others, the comprehension of how temporal and spatial factors can determine fish occupancy is detrimental to guide management and conservation actions.…”
Section: Introductionmentioning
confidence: 99%